Ciberacontecimento e sentidos da reportagem: mulheres trans presas enfrentam preconceito, abandono e violência - Souza, Juliana Borba de (Universidade do Vale do Rio dos Sinos, 2023)
This dissertation investigates the cyberevent (HENN, 2014) and the senses triggered by the repercussions of the report Trans women prisoners face prejudice, abandonment, and violence, broadcasted on the program Fantástico, from Rede Globo, on March 1st, 2020. The report, presented by Drauzio Varella, portrays the reality of trans women prisoners, sentenced in male prisons in Brazil. When interviewing Suzy de Oliveira dos Santos, and when they both realize that she had not received any visitors for over eight years, Drauzio hugs her and says: "Loneliness, right, my daughter? The gesture resonates in digital social networks. To understand the eventual potency (HENN, 2013a) of the case, it was necessary to identify which senses were triggered by the repercussion of the report. Therefore, our methodological approach uses the Analysis of Sense Construction in Digital Networks (HENN, 2014). The corpus was collected in the original publication of the official profile of Fantástico, from Rede Globo, on Twitter, on March 2, 2020. The 35-second video features the exact passage in which Drauzio hugs and says the phrase to Suzy de Oliveira dos Santos, in which 2,035 comments were collected via Twitter's API. To identify the singularities and which elements explain the propulsion of meanings, we analyzed the first 200 comments of each period of the repercussion, named: Heaven-2 to March 7, 2020; Purgatory-8 to March 9, 2020; Hell-10 to March 30, 2020. According to the outbreak of senses, we understand how the cyberevent (HENN, 2014), from the repercussion of the report, affected journalism. It is also possible to observe the interconnections between hate speech, gender agendas, and the disputes created in the dynamics of digital social networks. Moreover, the research concludes that the processes of disinformation and partisan discussions, enhanced by the pandemic of the SARS-CoV-2 virus, causing coronavirus (COVID-19) in 2020, amplified the dimensions of this episode.
Keywords: Ciberacontecimento; Jornalismo; Redes sociais; Discurso de ódio; Gênero; cyber event; Journalism; Social media; Hate speech; Gender; ACCNPQ::Ciências Sociais Aplicadas::Comunicação